Changes of the coverage of three wetland areas in cauca valley (2009)
The objective of this project was to apply geographic information system (GIS) technology, mainly ARCGIS and ERDAS software, as a methodology to identify changes in coverage and land usage of the terrain comprising the wetlands La Bolsa, Charco de Oro, and El Pital, located in the flat zone of the Andalucia municipality, in the villages of Campo Alegre and el Salto (Valle del Cauca Department, Colombia). The study employed aerial photos from 1950 and 1998, Landsat images from 2002, and base cartography of the zone. The processes within the methodology were purged. For example, the geo-referencing of photographs, and the creation of photo-mosaics to convey an image with a better visual appearance, and easier identification of the wetlands, in such a way that when making comparisons, they reveal changes in coverage in the study zone. The usage of GIS and correct processing of satellite images will be very helpful not only to evidence changes in soil usage in wetlands, but also in different areas where use of these technologies is very unusual.